Labdane Diterpenoids from Leonotis ocymifolia with Selective Cytotoxic Activity Against HCC70 Breast Cancer Cell Line - Jane Busisiwe Ncongwane; Vuyelwa Jacqueline Tembu; Comfort Mduduzi Nkambule; Douglas Kemboi; Gerda Fouche; Nyeleti Vukea; Jo-Anne de la Mare (Diseases)
Background: Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer with limited therapeutic options. Leonotis ocymifolia is a shrub widely used in traditional medicine to alleviate cancer-related symptoms. In a search to find safe and efficacious therapeutic agents from medicinal plants, Leonotis ocymifolia was studied to find compounds with anticancer activity against TNBC. Methods: Compounds from Leonotis ocymifolia were characterized using spectroscopic data such as IR, 1D and 2D NMR, and MS spectrometry and evaluated for cytotoxic activity against triple-negative breast cancer (HCC70), hormone receptor-positive breast cancer (MCF-7), and non-tumorigenic mammary epithelial cell lines (MCF-12A). Results: A previously unreported bis-spirolabdane, 13S-nepetaefolin (1), together with five known labdane diterpenoids, namely nepetaefolin (2), dubiin (3), nepetaefuran (4), leonotin (5), and leonotinin (6), from the genus Leonotis were isolated. Overall, the labdane diterpenoids showed selective activity toward triple-negative breast cancer cells (HCC70). Of the compounds extracted, 13S-nepetaefolin demonstrated the greatest cytotoxic activity with an IC50 of 24.65 µM (SI = 1.08) against HCC70 cells; however, it was equally cytotoxic to non-tumorigenic MCF-12A breast cells (IC50 of 26.55 µM), whereas its isomer (2) showed no activity. This suggests that stereochemistry might have an effect on the cytotoxic activity of the bis-spirolabdane diterpenoids. All the compounds (1–6) demonstrated adsorption, distribution, metabolism, and excretion properties (ADME), while leonotin (5) and leonotinin (6) exhibited lead-like properties and high synthetic accessibility scores. Conclusions: The findings from this study warrant further investigation of L. ocymifolia for potential triple-negative breast cancer (TNBC) therapeutic agents, including potential chemical derivatization of bis-spiro labdane diterpenoid (1) to improve selectivity to TNBC over non-cancer cells.